PENGEMBANGAN SISTEM INFORMASI CATERING BERBASIS WEB UNTUK MENINGKATKAN EFISIENSI DAN KEMUDAHAN LAYANAN CATERING - Winarnie, Winarnie; Mulyowati, Gandes; Khairu Nisa, Nisrina; Melani, Lestari Eka; Putri, Farah Tisya Anindya; Rahayu, Kurnia Puji (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2025)
The advancement of information technology has encouraged various sectors to adopt web-based systems to improve efficiency and service quality. This study discusses the development of a web-based catering information system aimed at providing convenience for customers in ordering catering services and supporting the operational efficiency of service providers. The system includes features such as online ordering, inventory management, online payment integration, and performance reporting. With a budget of IDR 90,500,000 and a project duration of five months, the system is expected to enhance customer satisfaction and provide reliable management tools for catering providers.